2014
DOI: 10.1002/chem.201402292
|View full text |Cite
|
Sign up to set email alerts
|

Guest Modulation of Spin‐Crossover Transition Temperature in a Porous Iron(II) Metal–Organic Framework: Experimental and Periodic DFT Studies

Abstract: The synthesis, structure, and magnetic properties of three clathrate derivatives of the spin-crossover porous coordination polymer {Fe(pyrazine)[Pt(CN)4]} (1) with five-membered aromatic molecules furan, pyrrole, and thiophene is reported. The three derivatives have a cooperative spin-crossover transition with hysteresis loops 14-29 K wide and average critical temperatures Tc =201 K (1⋅fur), 167 K (1⋅pyr), and 114.6 K (1⋅thio) well below that of the parent compound 1 (Tc =295 K), confirming stabilization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 71 publications
2
58
0
1
Order By: Relevance
“…The intrinsic chemical diversity and porosity make metal-organic frameworks (MOFs) promising materials for several technological applications, including gas storage (e.g., methane and hydrogen storage), 1-11 carbon capture, [12][13][14][15][16][17] hydrocarbon separation, [18][19][20] catalysis, [21][22][23][24][25][26][27] electrical [28][29] and proton [30][31][32][33][34][35][36][37][38][39][40][41][42] conductivity, magnetism [43][44][45][46][47][48] and luminescence. 49 However, despite their versatility, several frameworks display low stability when exposed to moisture, which has limited the use of MOFs in industrial applications thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic chemical diversity and porosity make metal-organic frameworks (MOFs) promising materials for several technological applications, including gas storage (e.g., methane and hydrogen storage), 1-11 carbon capture, [12][13][14][15][16][17] hydrocarbon separation, [18][19][20] catalysis, [21][22][23][24][25][26][27] electrical [28][29] and proton [30][31][32][33][34][35][36][37][38][39][40][41][42] conductivity, magnetism [43][44][45][46][47][48] and luminescence. 49 However, despite their versatility, several frameworks display low stability when exposed to moisture, which has limited the use of MOFs in industrial applications thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Iron‐containing cyanoheterometallic frameworks, including analogues of Hofmann clathrates, are another family of intensively studied SCO materials that can possess bi‐stability over a wide range of temperatures up to and above room temperature . They are also known for their sensitivity to the inclusion of guests into large guest‐accessible pores within a coordination framework . The variety of these SCO complexes is related to the number of different cyanometallates (Ni II , Pd II , Pt II , Cu I , Ag I , Au I , Cr III , Nb IV ) and N‐donor aromatic ligands (pyridines, pyrimidines, pyridazine, triazoles) that are suitable for the construction of these rigid polymeric structures …”
Section: Introductionmentioning
confidence: 99%
“…Hoffman‐type iron(II) SCO‐CPs/MOFs of type [Fe(pz)M(CN) 4 ] ( Fe–M ; M = Ni, Pt, Pd, pz = pyrazine) are representative host materials that exhibit SCO behaviors linked to guest occupancy of the stable pores in these materials (Figure a). The effects of the accommodation of diverse guest species, including solvents, gases, halogens and organic molecules on both the structures and the SCO behaviors of the Fe–M materials have been investigated. For instance, it was demonstrated that Fe–Ni adsorbed toluene, acetone, ethanol, methanol and acetonitrile molecules leading to the resulting host–guest composites showing SCO behaviors with different transition temperatures (Figure b).…”
Section: Guest‐modulated Magnetic Properties Of Metal Complex Assementioning
confidence: 99%